2016
DOI: 10.1016/j.jphs.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and comparison of sodium-glucose cotransporter 2 inhibitors: Part 2. Antidiabetic effects in type 2 diabetic mice

Abstract: Previously we investigated the pharmacokinetic, pharmacodynamic, and pharmacologic properties of all six sodium-glucose cotransporter (SGLT) 2 inhibitors commercially available in Japan using normal and diabetic mice. We classified the SGLT2 inhibitors with respect to duration of action as either long-acting (ipragliflozin and dapagliflozin) or intermediate-acting (tofogliflozin, canagliflozin, empagliflozin, and luseogliflozin). In the present study, antidiabetic effects of repeated administration of these SG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 27 publications
3
47
0
Order By: Relevance
“…Repeated administration of ipragliflozin lowered HbA 1c levels by increasing urinary glucose excretion. Further, ipragliflozin improved glucose tolerance, hyperinsulinemia, and insulin resistance, similar to findings reported in previous studies in type 2 diabetes models (Tahara et al, , ; Tahara, Takasu, Yokono, Imamura, & Kurosaki, ). Additionally, no hypoglycemic symptoms such as excessive weight loss or decreased locomotor activity were noted throughout the present study period.…”
Section: Discussionsupporting
confidence: 90%
“…Repeated administration of ipragliflozin lowered HbA 1c levels by increasing urinary glucose excretion. Further, ipragliflozin improved glucose tolerance, hyperinsulinemia, and insulin resistance, similar to findings reported in previous studies in type 2 diabetes models (Tahara et al, , ; Tahara, Takasu, Yokono, Imamura, & Kurosaki, ). Additionally, no hypoglycemic symptoms such as excessive weight loss or decreased locomotor activity were noted throughout the present study period.…”
Section: Discussionsupporting
confidence: 90%
“…liraglutide) as well as dipeptidyl dipeptidase 4 (DPP4) inhibitors, which act by increasing the bioavailability of incretins, have variably displayed the ability to elevate circulating adiponectin levels (Kim Chung le et al , ; Li et al , ; Sahebkar et al , ). Similarly, empagliflozin, a sodium‐glucose cotransporter 2 inhibitor used in the treatment of T2DM, reportedly increases adiponectin levels (Tahara et al , ). It is unclear whether such effects can be attributed to the improvement of systemic insulin sensitivity or are due to unidentified direct effects on AT.…”
Section: Adiponectin As a Therapeutic Targetmentioning
confidence: 99%
“…Pharmacokinetic parameters, such as the area under plasma concentration-time curve from zero to infinity (AUC), were calculated from plasma concentration vs time curves using non-compartment analysis with WinNonlin (version 5.1; Pharsights, Cary, NC, USA). The AUC ratios (i.e., ratios of kidney AUC to plasma AUC) were calculated by dividing the AUC of the three Recently, Tahara et al [5] compared the pharmacokinetics, pharmacodynamics, and pharmacological characteristics of six SGLT2 inhibitors, such as ipragliflozin, dapagliflozin, tofogliflozin, canagliflozin, empagliflozin, and luseogliflozin. The study showed that all the SGLT2 inhibitors induced urinary glucose excretion in a dose-dependent manner but the duration of action differed among the six drugs.…”
Section: Pharmacokinetic Studymentioning
confidence: 99%